The Influence of Saliva pH on the Fracture Resistance of Three Complete Denture Base Acrylic Resins - Juliana de Sá; Francisca Vieira; Carlos Manuel Aroso; Mónica Cardoso; José Manuel Mendes; António Sérgio Silva (International Journal of Dentistry)
Aim and Background. The absorption of fluids by denture base materials diminishes the mechanical properties such as hardness, strength, and fatigue limit due to the plasticizing effect of water. This study aimed to evaluate the influence of oral pH on the fracture resistance of prosthetic bases made of three different heat-polymerizable acrylic resin brands: RS Vertex®, Triplex Hot®, and Megacryl®. The strength needed to fracture the resins and the resistance to fracture each resin were evaluated. Methods. Ten prosthesis bases prepared with each brand of resin were subjected to neutral and low pH conditions (pH 7 and pH 4) by submerging them in artificial saliva for 30 days. After exposure, the fatigue resistance of the resins was tested using a Dental CS® Testing Machine. Statistical Analysis Test. The data sets were described quantitatively in terms of mean (M) and standard deviation (SD). Shapiro–Wilk tests and unilateral analysis of variance (ANOVA) were performed and complemented by Tukey’s multiple comparison tests. The effect size (η2), whose cohort points followed Cohen’s recommendations: 0.01 (low), 0.06 (medium), and 0.14 (high), was calculated. The results were considered significant if p<0.05 and marginally significant if p<0.10. Results. One-way ANOVA showed that Megacryl® had the highest fracture resistance at pH 7 (52.23 Kgf), compared with Triplex Hot® (p<0.001) and RS Vertex® (p=0.034). Two-way ANOVA confirmed the interaction between brand and pH (p=0.022), also revealing that brands comparison is significant or marginally significant, when pH is not considered (Megacryl® versus Triplex Hot®, p<0.001, and RS Vertex®, p=0.058; Triplex Hot® versus RS Vertex®, p=0.051), and pH 7 results were significantly higher (p=0.003), even when brands are not considered. Hence, Megacryl® at pH 7 was found to have the highest fracture resistance, detached from other brands and pH values. Conclusion. It can be concluded within the limitations of this study that there are differences in the fracture resistance among the three brands of acrylic resin. Megacryl® was found to have the highest fracture resistance, and Triplex Hot® was the lowest. The results also show that exposure to a low pH environment decreases the fracture resistance of the Megacryl® and RS Vertex® resins.